Науково-дослідницька діяльність з географічного краєзнавства у Каланчацькій ЗОШ І-ІІІ ст. № 2 - Она, О. (Краєзнавство, 2017)
У статті обґрунтовується необхідність географічного краєзнавства в рамках предмету географія
для розвитку патріотизму у школярів. Велику цінність в даному напрямку мають матеріали історії
рідного краю для формування ціннісного відношення до своєї Батьківщини. Детально описані основні
форми краєзнавчої роботи в рамках науково-дослідницької роботи в школі. The article substantiates the need for regional work in the context of geography study for patriotism development
in pupils. Materials on history of native land for valued attitude forming toward history of the motherland
are presented by the author. The main objective of this work is to describe actuality of a region study for forming
of patriotism for the schoolchildren of school № 2 in Кalanchak of Kherson region in the context of scientificallyresearch
work. The basic forms of regional work within the framework of research work at school are described
in detail. It noted that using of regional material for a study any subject in extracurricular work assists the decision
of tasks of education. The author said that she practices the realization of historical, natural and productive excursions.
One of effective forms of patriotic education is combination of study region and tourism. Expeditions are
the most difficult form of tourist-regional work. A regional study game assists detection of children’s hidden possibilities
and capabilities. In conclusion it is stated that the region study helps pupils to form a national character. В статье обосновывается необходимость краеведческой работы в контексте изучения предмета
география для развития патриотизма у школьников. Огромную ценность в данном направлении представляют материалы по истории родного края для формирования ценностного отношения к истории
своей родины. Подробно описаны основные формы краеведческой работы в рамках научно-исследовательской работы в школе.